Age determination of young rocks and artifacts: physical and chemical clocks in quaternary geology and archaeology - Wagner, Günther A. (Natural Science in Archaeology Ser., 1998)
Age Determination of Young Rocks and Artifacts Physical and Chemical Clocks in Quaternary Geology and Archaeology -- Age Determination of Young Rocks and Artifacts -- Copyright -- Preface -- Contents -- Abbreviations -- 1 Introduction -- 2 Materials -- 3 Radiogenic Noble Gases -- 4 Uranium Series -- 5 Cosmogenic Nuclides -- 6 Particle Tracks -- 7 Radiation Dosimetry -- 8 Chemical Reactions -- 9 Paleomagnetism -- 10 Earth's Orbit, Climate and Age -- References -- Subject Index.